Intention to get naloxone among patients prescribed opioids for chronic pain - Yinan Huang; Ning Lyu; Shrey Gohil; Shweta Bapat; E. James Essien; J. Douglas Thornton (BMC, 2022)
Abstract Background Prescription opioids have been increasingly prescribed for chronic pain while the opioid-related death rates grow. Naloxone, an opioid antagonist, is increasingly recommended in these patients, yet there is limited research that investigates the intention to get naloxone. This study aimed to investigate intention toward getting naloxone in patients prescribed opioids for chronic pain and to assess the predictive utility of the theory of reasoned action (TRA) constructs in explaining intention to get naloxone. Methods This was a cross-sectional study of a panel of U.S. adult patients prescribed opioids for chronic pain using a Qualtrics® XM survey. These patients participated in the study during February to March 2020. The online internet survey assessed the main outcome of intention to get naloxone and constructs of TRA (attitudes and subjective norms); additional measures assessed the characteristics of patients' opioid overdose risk factors, knowledge of naloxone, and their demographics. The relationship between TRA constructs, namely, attitudes and subjective norms, and the intention variable was examined using logistic regression analyses with the intention outcome contrasted as follows: high intention (scores ≥ 5) and non-high intention (scores < 5). Results A total of 549 participants completed the survey. Most of them were female (53.01%), White or Caucasian (83.61%), non-Hispanic (87.57%) and had a mean age of 44.16 years (SD = 13.37). Of these, 167 (30.42%) had high intention to get naloxone. The TRA construct of subjective norm was significantly associated with increased likelihood of higher intentions to get naloxone (OR 3.04, 95% CI 2.50-3.70, P < 0.0001). Conclusions Our study provides empirical support of the TRA in predicting intention to get naloxone among chronic pain patients currently taking opioids. Subjective norms significantly predicted intention to get naloxone in these patients. The interventions targeting important reference groups of these patients would have greater impact on increasing intention to get naloxone in this population. Future studies should test whether theory-based interventions focusing on strengthening subjective norms increase intention to get naloxone in this population.